2018
DOI: 10.1016/j.cej.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility, biodegradation and excretion of polylactic acid (PLA) in medical implants and theranostic systems

Abstract: Polylactic acid (PLA) is the most commonly used biodegradable polymer in clinical applications today. Examples range from drug delivery systems, tissue engineering, temporary and long-term implantable devices; constantly expanding to new fields. This is owed greatly to the polymer's favorable biocompatibility and to its safe degradation products. Once coming in contact with biological media, the polymer begins breaking down, usually by hydrolysis, into lactic acid (LA) or to carbon dioxide and water. These pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
378
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(389 citation statements)
references
References 90 publications
(75 reference statements)
4
378
0
7
Order By: Relevance
“…29 Although PLA has high biocompatibility and can be used in drug delivery systems as well, calcium phosphate further enhances the activity of osteoblasts and the bone growth. 30,31 Only considering the degradation rate, the additional PLA coating is the more effective variant as compared with the calcium phosphate coating. Tomographic images of LAE442 implants with the same coatings as used in the present study showed another benefit of the PLA coating: The effect of the grain size on the corrosion rate could be successfully suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although PLA has high biocompatibility and can be used in drug delivery systems as well, calcium phosphate further enhances the activity of osteoblasts and the bone growth. 30,31 Only considering the degradation rate, the additional PLA coating is the more effective variant as compared with the calcium phosphate coating. Tomographic images of LAE442 implants with the same coatings as used in the present study showed another benefit of the PLA coating: The effect of the grain size on the corrosion rate could be successfully suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of PLA is further enhanced by enzymes secreted by a bacterial infection or inflammation cells. Disintegration takes place both on the surface and inside the polymer through water diffusion between polymer chains 62 . However, features such as poor toughness, low degradation rate, and high hydrophobicity limit the implementation of PLA in wound dressings.…”
Section: Morphology Of Agnps Containing Nanofilmsmentioning
confidence: 99%
“…Poly(lactic acid) (PLA), a biodegradable polymer, can be synthesized from lactic acid in fermented starch or sugar to L and D lactic acids, polymerized in forms of poly(L‐lactic acid) (PLLA), poly(D‐lactic acid) (PDLA) and poly(DL‐lactic acid) (PDLLA) . PLA has gained attention from many researchers in packaging and medical applications . However, the crystallization of PLA is slow, resulting in poor thermal stability and heat resistance.…”
Section: Introductionmentioning
confidence: 99%